2012
DOI: 10.1177/0533316411424356
|View full text |Cite
|
Sign up to set email alerts
|

Report on a Systematic Review of the Efficacy and Clinical Effectiveness of Group Analysis and Analytic/Dynamic Group Psychotherapy

Abstract: This article reports on a systematic review to assess the efficacy and clinical effectiveness of group analysis and analytic/dynamic (A/D) group psychotherapy. Systematic literature searches were undertaken; 34 primary studies and 19 reviews met the inclusion criteria and their data was extracted. Of the primary studies, the randomized controlled trials provided evidence for the efficacy and clinical effectiveness of group therapy approaches in a range of clinical problems, but not for specific benefits of any… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0
10

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 46 publications
1
28
0
10
Order By: Relevance
“…The fact that age limit was not an inclusion criteria may explain the high mean age of our patients (49.1 years), and it has been shown that dynamic group psychotherapy is beneficial for elderly people (Canete, Stormont, & Esquerro, ). Patients discontinued group therapy mostly during the first sessions, as previously reported (Blackmore, Tantam, Parry, & Chambers, ), although a more comprehensive assessment of the indication of psychotherapy or in‐depth evaluation of the patients' motivation may reduce the number of patients lost to continue with treatment. The number of patients lost to follow‐up was greater among controls.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…The fact that age limit was not an inclusion criteria may explain the high mean age of our patients (49.1 years), and it has been shown that dynamic group psychotherapy is beneficial for elderly people (Canete, Stormont, & Esquerro, ). Patients discontinued group therapy mostly during the first sessions, as previously reported (Blackmore, Tantam, Parry, & Chambers, ), although a more comprehensive assessment of the indication of psychotherapy or in‐depth evaluation of the patients' motivation may reduce the number of patients lost to continue with treatment. The number of patients lost to follow‐up was greater among controls.…”
Section: Discussionmentioning
confidence: 65%
“…Patients discontinued group therapy mostly during the first sessions, as previously reported (Blackmore, Tantam, Parry, & Chambers, 2012), although a more comprehensive assessment of the indication of psychotherapy or indepth evaluation of the patients' motivation may reduce the number of patients lost to continue with treatment. The number of patients lost to follow-up was greater among controls.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…A review of analytic and psychodynamic group therapy provides evidence for the effectiveness of treatment in groups, but not necessarily for the superiority of analytic and psychodynamic group therapy [1]. In a recent randomized controlled trial, Watzke et al selected patients for treatment in either psychodynamic or cognitive behavioral groups [2].…”
Section: Introductionmentioning
confidence: 99%
“…Bezüglich der Forschung nehmen Blackmore et al (2012) in Group Analysis noch einmal in einer Kurzfassung Stellung zu ihrer Metaanalyse zur Wirksamkeit (efficacy) und klinischen Effektivität (effectiveness) von Gruppenanalyse und analytischer/ psychodynamischer Gruppenpsychotherapie, die sie im Auftrag von International Group Analysis (IGA) und Group Analytic Society (GAS) (beide London) durchgeführt hatten (Blackmore et al, 2009 (MacKenzie, 1997). Beide Formate sind psychodynamisch, d. h. sie fokussieren sowohl auf bewusste als auch unbewusste Prozesse des Einzelnen wie der Gruppe.…”
unclassified